2021
DOI: 10.1039/d1tb00312g
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of SYBR green chromophore reveals major improvement with one heteroatom difference

Abstract: Five nucleic acid binding cyanine dyes were synthesized and their photophysical properties were evaluated. Changing a single heteroatom in the chromophore causes major differences both in brightness and photostability between...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…Similar enhancement of Stoke's shift was also found by Zhang et al [23] and Peng et al [24] when replacing chloride by amine group. The same was also observed in our previous studies [15]. Together with the Stoke's shifts, quantum yield is an important way to evaluate fluorescent probes since it tells how much of the absorbed photons are emitted and therefore it can illuminate which dyes could be potentially strongly fluorescent.…”
Section: Photophysical Studiessupporting
confidence: 80%
See 4 more Smart Citations
“…Similar enhancement of Stoke's shift was also found by Zhang et al [23] and Peng et al [24] when replacing chloride by amine group. The same was also observed in our previous studies [15]. Together with the Stoke's shifts, quantum yield is an important way to evaluate fluorescent probes since it tells how much of the absorbed photons are emitted and therefore it can illuminate which dyes could be potentially strongly fluorescent.…”
Section: Photophysical Studiessupporting
confidence: 80%
“…In this study, we have synthesized five new nucleic acid-binding cyanine dyes to study how different functional groups affect to the nature of the quality of the dyes in photophysical measurements. In our previous paper, we concluded that a single heteroatom could change the qualities of the dyes drastically and oxazolium moiety seemed to produce better dyes [15]. With that in mind, we were interested to see the effect of the thiazolium moiety.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations